Dinamika Konstitusional Wakil Presiden Dalam Perspektif Sistem Pemerintahan Presidensial Menurut Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Azi Ferdinandi Kusnadi; Eki Furqon (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2021)
The vice president and Presidentare inter-officerelations. Tetapi the position of Vice President both before and after the change is not clearly described,, padahal authoritative authority environment is a condition of the creation of an authoritative relationship. Therefore, this paper was created with the aim to see how the constitutional dynamics of the Vice President's position in the Indonesian constitutional system. The method used is legal research(legal research)with a type of research library (library research).The results showed that there is a vagueness of the role of the Vice Presidentas an aide to thePresident in article 4 paragraph 2 of the Constitution of the Republic of Indonesia year 1945. Whether the context of the word "assisted" can be interpreted broadly or narrowly. This will have implications on the environmental relations of office and officials Wakil President and President governing the organization and working system of presidential institutions. The author recommends the establishment of special rules to regulate the position of the Vice President and the pattern of relations with the President in order to further clarify the role of each so as to create a harmonious relationship and ensure the legal certainty of governance through the Presidential Bill.